Pengaruh IPM, TPAK Perempuan, dan TPT Perempuan Terhadap Kemiskinan: Kabupten dan Kota di Jawa Tengah 2019-2023 - Pristyana Nur Alif Risqi (Indonesian Journal of Islamic Economics and Business, 2026)
Poverty continues to be a long-standing challenge for development, shaped by multiple social and economic elements, such as the quality of human capital and the state of women in the workforce. This research intends to analyze how the HDI, the FLFPR, and the FOUR impact poverty levels in the regencies and municipalities of Central Java Province from 2019 to 2023. The research utilized secondary data sourced from the BPS of Indonesia and employed a panel data regression method that merges cross-sectional information from 35 districts and sub-districts with time-series data covering the years 2019 to 2023. Findings from the Chow and Hausman tests suggest that the FEM is the optimal estimation framework. The HDI negatively and significantly affects poverty, while the female open unemployment rate positively and significantly impacts it. Conversely, the female labor force participation rate does not have a significant effect on poverty levels. The results indicate that enhancing the quality of human development and decreasing unemployment among women are vital for alleviating poverty. This study's unique contribution is its emphasis on the connection between human development and female labor market metrics to explain poverty at the regency and municipal levels in Central Java Province between 2019 and 2023.